Influence of Propeller Slipstream on the Flow Field of S-Shaped Intake - Shuili Ren (Hindawi Limited, 2021)
For turboprop engine, the S-shaped intake affects the engine performance and the propeller is not far in front of the inlet of the S-shaped intake, so the slipstream inevitably affects the flow field in the S-shaped intake and the engine performance. Here, an S-shaped intake with/without propeller is studied by solving Reynolds-averaged Navier-Stokes equation employed SST k-ω turbulence model. The results are presented as time-averaged results and transient results. By comparing the flow field in S-shaped intake with/without propeller, the transient results show that total pressure recovery coefficient and distortion coefficient on the AIP section vary periodically with time. The time-averaged results show that the influence of propeller slipstream on the performance of S-shaped intake is mainly circumferential interference and streamwise interference. Circumferential interference mainly affects the secondary flow in the S-shaped intake and then affects the airflow uniformity; the streamwise interference mainly affects the streamwise flow separation in the S-shaped intake and then affects the total pressure recovery. The total pressure recovery coefficient on the AIP section for the S-shaped intake with propeller is 1%-2.5% higher than that for S-shaped intake without propeller, and the total pressure distortion coefficient on the AIP section for the S-shaped intake with propeller is 1%-12% higher than that for the S-shaped intake without propeller. However, compared with the free stream flow velocity (Ma=0.527), the influence of the propeller slipstream belongs to the category of small disturbance, which is acceptable for engineering applications.